Using Protein Painting Mass Spectrometry to Define Ligand Receptor Interaction Sites for Acetylcholine Binding Protein - Alexandru Graur; Natalie Erickson; Nadine Kabbani (Bio-Protocol)
Nicotinic acetylcholine receptors (nAChRs) are a family of ligand-gated ion channels expressed in nervous and non-nervous system tissue important for memory, movement, and sensory processes. The pharmacological targeting of nAChRs, using small molecules or peptides, is a promising approach for the development of compounds for the treatment of various human diseases including inflammatory and neurogenerative disorders such as Alzheimer’s disease. Using the Aplysia californica acetylcholine binding protein (Ac-AChBP) as an established structural surrogate for human homopentameric α7 nAChRs, we describe an innovative protein painting mass spectrometry (MS) method that can be used to identify interaction sites for various ligands at the extracellular nAChR site. We describe how the use of small molecule dyes can be optimized to uncover contact sites for ligand–protein interactions based on MS detection. Protein painting MS has been recently shown to be an effective tool for the identification of residues within Ac-AChBP involved in the binding of know ligands such as α-bungarotoxin. This strategy can be used with computational structural modeling to identify binding regions involved in drug targeting at the nAChR.